Magnetic Recording Reliability Evaluation - Ekkaphon Phonyiam; Ponrudee Netisopakul (2022 22nd International Conference on Control, Automation and Systems (ICCAS), 2022)
Magnetic recording heads in Hard Disk Drive (HDD) integrates of two main components included of writer and reader devices for injecting and reading the pattern on recording media. Both features were fabricated in a single piece and become a multi-layer structure. Reliability test for magnetic recording head has become a challenge that could introduce complex problems when failure occurred. This paper aims to conceptualize testing workflow and measurement for magnetic recording head reliability evaluation. The testing process lets head performing cycles of writing and reading operations in designated ambient until it meets stopping criteria. And the reliability analysis procedure focuses on lifetime analysis with Weibull distribution on different failure modes and characters extracting from time-series bit-error-rate profile which was obtained from reliability test.
Keywords: Adhesion, Friction, and Surface Interactions; Semiconductor materials and devices; Surface Roughness and Optical Measurements